Domestic ruptures: French emigrants to the Channel Island of Jersey and the gendering of exile, 1789-1802 - Sydney Watts (Diasporas: Circulations, Migrations, Histoire)
This essay focuses on the temporary settlement of refugees on the Channel Island of Jersey during the French Revolution, analyzing this borderland community with a gendered lens. Until recently, French historians have depicted the emigration as a direct response to French and British anti-émigré legislation and rhetoric, each wave contingent upon the political climate in France. This perspective, however, misses much of the complexity of Jersey’s unique place in the emigration as a French speaking island along the Brittany coast with a British military presence. A social analysis of this emigration from western and northern France to the Channel Island of Jersey reveals the complex motives of household migration and the realities of temporary exile in a fractured world. Domestic ruptures among these French emigrants were met with a mixed response from the host country (Britain) and the local authorities who managed these refugees. Viewing their losses evoked a crisis of masculinity and demanded a humanitarian response that highlighted female fragility.